2020
DOI: 10.1186/s12966-020-00974-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of snack portion size on anticipated and experienced hunger, eating enjoyment, and perceived healthiness among children

Abstract: Background Large portion sizes encourage overconsumption. Prior studies suggest that this may be due to errors in anticipating the effects of portion size, although the studies were limited to adults and energy-dense foods. Objective Our aim was to investigate potential anticipation errors related to the effects of portion size on hunger, eating enjoyment, and healthiness ratings among 8-to-11-year-old children, for snacks differing in energy densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…My stomach is truly really empty and is rumbling at lot” [see ( 25 , 32 ) for details]. Then, they ate the apple preload entirely and rated their liking on a dedicated child-tailored 10-cm VAS punctuated by smileys [see ( 25 , 32 )] and evaluated again their level of hunger ( Figure 1 ). After this, and for 10 min that were strictly controlled, they played an online game based on the principle of “where's Wally?”.…”
Section: Methodsmentioning
confidence: 99%
“…My stomach is truly really empty and is rumbling at lot” [see ( 25 , 32 ) for details]. Then, they ate the apple preload entirely and rated their liking on a dedicated child-tailored 10-cm VAS punctuated by smileys [see ( 25 , 32 )] and evaluated again their level of hunger ( Figure 1 ). After this, and for 10 min that were strictly controlled, they played an online game based on the principle of “where's Wally?”.…”
Section: Methodsmentioning
confidence: 99%
“…In preschool children, a randomised control trial offering smaller portion sizes or swapping out HED items for fruits and vegetables demonstrated that this strategy was well accepted and produced significant benefits to the diets of children (Reale et al, 2018). However, for older children (8-11 yr) offering smaller sized apple sauce and brownies was less acceptable than large portions (Schwartz et al (2020). Unlike adults (Cornil & Chandon, 2016) children appear to appreciate quantity over quality and shifting that focus is likely to be challenging.…”
Section: Introductionmentioning
confidence: 98%
“…Two recent studies investigated how consumers, both children and adults, anticipate the effects of portion size reductions on hunger change and eating enjoyment (Haynes et al, 2020;Schwartz et al, 2020). Schwartz and colleagues (2020) found that children anticipate the effects of smaller versus larger portion sizes on residual hunger accurately, but overestimate the effects of portion size on eating enjoyment, in the sense that larger portions increased anticipated but not experienced eating enjoyment.…”
Section: Introductionmentioning
confidence: 99%